Multifunctional ionic porous frameworks for CO2 conversion and combating microbes. Issue 30 (14th July 2020) - Hussain, MD. Waseem; Bhardwaj, Vipin; Giri, Arkaprabha; Chande, Ajit; Patra, Abhijit
Abstract : We have demonstrated the catalytic CO2 conversion, and antibacterial and antiviral activity, including against HIV-1, of zinc oxide-infused ionic porous organic frameworks. Abstract : Porous organic frameworks (POFs) with a heteroatom rich ionic backbone have emerged as advanced materials for catalysis, molecular separation, and antimicrobial applications. The loading of metal ions further enhances Lewis acidity, augmenting the activity associated with such frameworks. Metal-loaded ionic POFs, however, often suffer from physicochemical instability, thereby limiting their scope for diverse applications. Herein, we report the fabrication of triaminoguanidinium-based ionic POFs through Schiff base condensation in a cost-effective and scalable manner. The resultant N-rich ionic frameworks facilitate selective CO2 uptake and afford high metal (Zn(ii ): 47.2%) loading capacity. Owing to the ionic guanidinium core and ZnO infused mesoporous frameworks, Zn/POFs showed pronounced catalytic activity in the cycloaddition of CO2 and epoxides into cyclic organic carbonates under solvent-free conditions with high catalyst recyclability. The synergistic effect of infused ZnO and cationic triaminoguanidinium frameworks in Zn/POFs led to robust antibacterial (Gram-positive, Staphylococcus aureus and Gram-negative, Escherichia coli ) and antiviral activity targeting HIV-1 and VSV-G enveloped lentiviral particles. We thus present triaminoguanidinium-based POFs and Zn/POFs as a new class of multifunctional materials for environmental remediation and biomedical applications.